Exploring the Relationship between Digital Communication Intensity and Learning Effectiveness in Higher Education: Towards Sustainable Digital Pedagogy (SDG 4) - Muhammad Fadli; Ratu Chaterine Fajri; Arifin Arifin; Prisma Yunia Putri; Made Dewi Purnami (Postgraduate, University of Mataram, 2026)
This study analyzes the relationship between digital communication intensity and learning effectiveness, aligning with SDG 4 (Quality Education). Employing a quantitative approach, 350 university students participated. Descriptive analysis showed a mean digital communication intensity of 3.00 (SD = 0.75) and learning effectiveness of 3.65 (SD = 0.72). Contrary to linear assumptions, Pearson correlation revealed a non-significant linear relationship (r = 0.12; p = 0.06). However, polynomial regression confirmed a significant inverted-U pattern (β₂ = -0.18; p < 0.001; R² = 0.68), with an optimum point at 3.66, indicating peak effectiveness at moderate intensity. Hierarchical regression showed that learning motivation and internet infrastructure quality significantly controlled the variance, confirming the robustness of the curvilinear model. These findings underscore the need for regulated digital platform usage to prevent cognitive overload